Cover Picture: Sulfoxide‐Directed Metal‐Free ortho‐Propargylation of Aromatics and Heteroaromatics (Chem. Eur. J. 20/2015). Issue 20 (11th May 2015) - Eberhart, Andrew J.; Shrives, Harry J.; Álvarez, Estela; Carrër, Amandine; Zhang, Yuntong; Procter, David J.
<x xml:space="preserve">Abstract</x> Taking signage from the University of Manchester campus, the image illustrates a new, metal‐free direction for cross‐coupling technology. The sulfoxide‐directed, metal‐free ortho‐propargylation of aromatics exploits intermolecular delivery of a nucleophile to sulfur followed by an intramolecular relay to carbon. The operationally simple cross‐coupling procedure is general and highly selective. The 'safety‐catch' nature of the directing group is also illustrated. The background shows the University's Alan Turing Building. For more details, see the Full Paper by D. J. Procter and co‐workers on page 7428 ff.